Rekayasa Genetik pada Nyamuk Penyebab Malaria: Kajian Literatur - Romadhona, Harisma Atiqur; Qushayyi, Muhammad Faiq; Sari, Rahmawati Yanita; rohmah, sayyidah auliyar (Jurnal Pendidikan Ilmu Pengetahuan Alam (JP-IPA), 2024)
Indonesia is a country with a heterogeneous tropical climate and is also vulnerable to the impacts of regional and global climate change. Malaria is transmitted by the Anopheles sp mosquito, the clinical and pathological symptoms of malaria are almost exclusively caused by the asexual phase of plasmodium in erythrocytes. This research uses a qualitative descriptive approach, because the data used comes from descriptions of words, with the type of library research or literature review. Library research and library searches are not only carried out as initial steps in preparing a research framework but also serve as library sources that are used as sources of research data. Search for data via Google Scholar using the keywords "genetic engineering" and "malaria mosquito" then select and eliminate data sources that are appropriate to the topic, namely genetic engineering of mosquitoes that cause malaria. The results of the literature review found that: (1) Genetic engineering is a technology that involves the manipulation of DNA molecules, which is also known as recombinant DNA technology; (2) Various terms in gene molecular manipulation techniques, such as DNA recombination, gene cloning, and gene modification; (3) Genetic engineering using basic methods, such as DNA isolation, PCR, RT-PCR, hybridization techniques, and RFLP analysis; and (4) Genetic engineering of mosquitoes can be done in several ways, namely: the sterile male technique, the distribution of mosquitoes with dominantly lethal genes, and coding genes (Gen Drives).